Perceptions of young men at the Free State School of Nursing with regards to teenage pregnancy - Siphiwe T. Madlala; Maureen N. Sibiya; Thembelihle S.P. Ngxongo (AOSIS, 2018)
Background: Teenage pregnancy is a socio-economic challenge and a serious public health problem for communities in South Africa. It is, therefore, imperative that effective interventions and programmes be implemented to address this problem. A number of research studies have been conducted on teenage pregnancy in South Africa, but their focus was mainly on teenage girls excluding young men's involvement in teenage pregnancy. Aim: The aim of the study was to determine the perceptions of young men between the ages of 18 and 23 years towards teenage pregnancy. Methods: A qualitative, explorative semi-structured interview descriptive design was used toconduct the study. The study was guided by the Johnson's Behavioral System Model. Purposive sampling was used to select 10 participants with whom semi-structured interviews were conducted. Thematic analysis of data were performed. Setting: The study was conducted in Free State School of Nursing's two main campuses. Results: The findings of this study revealed that young men were not involved in reproductive health programmes aiming to prevent teenage pregnancies. Father and son's poor communication on issues related to sex and teenage pregnancy contributes to unprotected sexual intercourse resulting in teenage pregnancy. Cultural and traditional practices such as the withdrawal method, not using contraceptives, and misleading teachings at the initiation schools contribute to risk factors of teenage pregnancy. Conclusion: There is still a gap in reproductive health that needs to be filled by involving young men to reduce teenage pregnancies. Involving young men in reproductive health programmes could lead to a decreased number of teenage pregnancies. Factors, such as cultural and traditional practices, and father and son sexual health education, need to be taken into consideration to prevent teenage pregnancies.